Role of the Wnt Pathway in Thyroid Cancer - Sastre-Perona, Ana; Santisteban, Pilar (Frontiers in Endocrinology, 2012)
Aberrant activation of Wnt signaling is involved in the development of several epithelial tumors. Wnt signaling includes two major pathways (i) the canonical or Wnt/βcatenin pathway and (ii) the non-canonicals pathways, which do not involve βcatenin stabilization. Among these pathways, the Wnt/βcatenin pathway has received most attention during the past years for its critical role in cancer. A number of publications emphasize its role in thyroid cancer. Wnt signaling plays a crucial role in development and epithelial renewal, and components such as βcatenin and Axin are often mutated in thyroid cancer. Although it is accepted that alteration of Wnt signaling is a late event in thyroid cell transformation that affects anaplastic thyroid tumors, recent data also suggest its alteration in papillary thyroid carcinoma with RET/PTC mutations. Therefore, the purpose of this review is to summarize the main relevant data of Wnt/βcatenin signaling in thyroid cancer.